Proteomic Identification of Calumenin as a G551D - CFTR Associated Protein - Teng, Ling; Kerbiriou, Mathieu; Taiya, Mehdi; Le Hir, Sophie; Mignen, Olivier; Benz, Nathalie; Trouvé, Pascal; Férec, Claude (PLOS ONE, 2012)
Cystic fibrosis (CF) is the most common lethal autosomal recessive disease in the Caucasian population. It is due to mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. To date, over 1910 mutations have been identified in the CFTR gene. Among these mutations, the CF-causing missense mutation G551D-CFTR (approx. 5% of cases) encodes for a CFTR chloride channel with normal expression on the cell surface. Nevertheless, it is associated with severe disease due to its altered channel activation. The aim of the present study was to identify specific interacting proteins of G551D-CFTR. Co-immunoprecipitated proteins with G551D-CFTR were resolved by 2D-gel electrophoresis (2-DE). Mass Spectrometry revealed that calumenin was present in the protein complex linked to G551D-CFTR. Despite its basal expression was not modified in G551D-CFTR expressing cells when compared to Wt-CFTR expressing cells, it was more abundant in the G551D-CFTR complex detected by immunoprecipitation. The calumenin-CFTR interaction was also shown by Surface Plasmon Resonance and further confirmed by computational analysis of the predicted calumenin’s partners. Because in our cellular model calumenin was found in the endoplasmic reticulum (ER) by immunofluorescence experiments, we suggest that calumenin is likely involved in the mutated CFTR’s maturation. In conclusion, we showed for the first time that calumenin binds to CFTR and that it is increased in the G551D-CFTR complex. We suggest that it may be involved in the physiopathology of G551D-CFTR and that G551D-CFTR may follow a specific maturation and trafficking pathway. We also hypothesize that UPR may be triggered independently of the retention of G551D-CFTR in the ER because Grp78/Bip expression is increased in the cells. Finally, we propose here that Calumenin is a new CFTR chaperone.